Correlation between ALK, ROS1 Biomarkers and EGFR Oncogene Mutations in Lung Tumours: Our Observations in an Apex Oncopathology Laboratory - Kishore, Raja Ratna; Pan, Vinita (Asian Pacific Journal of Cancer Biology, 2023)
Introduction: Analysis of Anaplastic lymphoma receptor tyrosine kinase gene (ALK), Repressor of Silencing 1 (ROS1) gene are determined by immunohistochemistry (IHC) and it is an easily applicable, cost-effective assay for potential treatment with crizotinib. Mutations of Epidermal growth factor receptor (EGFR) genes are evaluated by IHC/Multiplex RT-PCR. The purpose of this study is to assess the frequencies of ALK, ROS1 and their association with EGFR fusion gene mutations in a spectrum of lung tumours. Materials and methods: A total of 202 cases of lung tumours reported at our Center for Oncopathology from September 1st 2020 to 31st August 2021, were retrospectively analyzed for ALK, ROS1 and EGFR fusion genes based on Immunohistochemistry (IHC) and Multiplex PCR findings. ALK was tested using D5F3 clone, and ROS1 was analyzed using Cell Signalling’s D4D6 clone on the Ventana immunohistochemistry platform. EGFR status was analyzed using EGFR mutation test V2 real-time multiplex PCR assay on Roche Cobas Z480. Results: 202 biopsy samples and cellblocks of fluid aspirates were analyzed. 175/202 were histologically and immunologically proved as Non-small cell lung carcinoma (Primary pulmonary adenocarcinoma) and its metastases. 09/199 (5.23%) were Positive for ALK IHC and 03/199 (1.74%) cases had equivocal results. 06/179 (3.85%) cases were Positive for ROS1 IHC and 03/179 (1.92%) cases had equivocal results. Other histo-morphological diagnoses i.e., adenosquamous, squamous, small cell, mucinous carcinoma etc (27 cases) were all ALK and ROS1 Negative. 188/202 tumours were analyzed for EGFR mutation status, which showed 70/188 (37.23%) had specific EGFR mutations. 118/188 (62.76%) cases were EGFR wildtype. Conclusion: We observed that age related incidence of EGFR mutations was highest in elderly females, of 61 to 70 years. ALK gene mutations occurred in 6.03% and ROS1 gene mutations occurred in 5.02% of lung tumours and their metastases. EGFR-mutations were associated with ROS1 mutated lung adenocarcinomas. There are no coexistent ALK-EGFR or ALK-ROS1 mutations. All ALK IHC positive pulmonary adenocarcinomas are ROS1 negative and are mutually exclusive.